The Best Way to Locate a Purpose in Sport: Considerations in Aesthetics? - Leon Culbertson; Graham McFee (Aesthetic Investigations, 2016)
The paper highlights the centrality of some concepts from philosophy of sport for philosophical aesthetics. Once Best (BJA, 1974) conclusively answered negatively the fundamental question, ‘Can any sport-form be an artform?’, what further issues remained at the intersection of these parts of philosophy? Recent work revitalizing this interface, especially Mumford’s Watching Sport (2012), contested Best’s fundamental distinction between purposive and aesthetic sports, and insisted that purist viewers are taking an aesthetic interest in sporting events. Here, we defend Best’s conception against considerations Mumford hoped would bring the aesthetics of art and sport closer together, thereby elaborating the aesthetics of sport. But, against Mumford’s resolutely psychological conception of an aim, we follow Best to defend the centrality, for purposive sports, of the means/ends contrast even when taking an aesthetic interest in such sports. We conclude with general speculations about the potential future of the discussions originated here.